2015
DOI: 10.1111/cei.12674
|View full text |Cite
|
Sign up to set email alerts
|

Permissive and protective roles for neutrophils in leishmaniasis

Abstract: Summary Leishmania parasites are the causative agents of leishmaniasis, a neglected tropical disease that causes substantial morbidity and considerable mortality in many developing areas of the world. Recent estimates suggest that roughly 10 million people suffer from cutaneous leishmaniasis (CL), and approximately 76 000 are afflicted with visceral leishmaniasis (VL), which is universally fatal without treatment. Efforts to develop therapeutics and vaccines have been greatly hampered by an incomplete understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 98 publications
(145 reference statements)
1
61
0
6
Order By: Relevance
“…The short half-life of neutrophils makes it hard to isolate neutrophils from intestines, as it requires a long processing time, and thus most neutrophils isolated would have died by the end of preparation. We thus use peritoneal neutrophils as they are ready to be prepared in large quantities in our in vitro studies (22). We stimulated peritoneal neutrophils with IL-23, IL-6, IL-21, TNFα, or IL-1β to assess which cytokine(s) trigger IL-17 and IL-22 production in neutrophils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The short half-life of neutrophils makes it hard to isolate neutrophils from intestines, as it requires a long processing time, and thus most neutrophils isolated would have died by the end of preparation. We thus use peritoneal neutrophils as they are ready to be prepared in large quantities in our in vitro studies (22). We stimulated peritoneal neutrophils with IL-23, IL-6, IL-21, TNFα, or IL-1β to assess which cytokine(s) trigger IL-17 and IL-22 production in neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…The neutrophils were prepared from the peritoneal cavity as we previously described (22). Briefly, C57BL/6 mice were injected with 1ml of 3% thioglycollate broth, and the peritoneal cavity was washed with cold PBS buffer containing 5% FBS 5 hours later.…”
Section: Methodsmentioning
confidence: 99%
“…The results were shown to vary depending on the Leishmania spp. and the genetic background of the host, reviewed in Hurrell et al [11] and Carlsen et al [15]. With the use of L. mexicana parasites, a New World Leishmania spp., we have previously shown that the early neutrophil recruitment following infection has a negative impact on disease outcome, contributing to the development of chronic lesions; associated absence of an efficient, protective immune response; and failure to control parasite load [7].…”
Section: Introductionmentioning
confidence: 99%
“…(12)]. Neutrophil function in human CL has been investigated in several studies (1315) and they indicate that neutrophils are active players in patients with both acute and chronic CL and are important immune regulators that can have beneficial as well as detrimental effects (16). Since different Leishmania species can drive distinct neutrophil functions (17), it is of utmost importance that the phenotypes and functions of neutrophils isolated from patients infected by different Leishmania species are investigated.…”
Section: Introductionmentioning
confidence: 99%